PROTEIN DIGESTION IN PERANAKAN ETAWA GOAT DUE TO DIFFERENT LEVELS OF DIETARY PROTEIN - Yusuf, Roosena (BIOMA, 2014)
The  effort  to  increases  milk  production  especially  milk  goat production  can  do  with  increasing  quality  of  dietary  and maintenance  of  goats,  one  of  them  was  increasing  level  of dietary  protein  to  increase  protein  metabolism  in  goats.  The research purpose was to find out the acurate of  dietary protein level to maximalize protein digestion  in Peranakan Etawa goat. The  materials  used  in  the  research  were  12  Peranakan  Etawa goats at fourth month pregnancy and range of body weight 35,20 ±  1,21  kg  (cv  =  3,44%)  with  ±  13  month  ages.  The  research design  that  used  is  completely  randomized  design  one  factor with three treatment and four restating. Parameter that evaluated include dry matter intake, consumption of crude protein, protein digestion. Result of the research shown that the average of dry matter intake to T1, T2 and T3 were 958,99; 981,51 and 1242,73 g/goat/day  (P<0,05).  The  average  of  consumption  of  crude protein  to  T1,  T2  and  T3  were  114,69;  144,44  and  233,11 g/goat/day(P<0,05). The average of protein digestion to T1, T2 and  T3  were  64,22  (55,18%);  92,83  (64,21%)  and  156,21 (66,97%)  g/goat/day  (P<0,05).  The  conclution  of  the  research was  levels  of  dietary  protein  as  18,43%  may  increase  the optimal protein digestion in Peranakan Etawa goat.Keywords : protein, Peranakan Etawa goat